The Role of Foreign Language Education in Human Capital Formation: A Narrative Literature Review - Tzidimopoulou, Vasiliki; Anastasiadou, Penelope (European Scientific Journal, ESJ, 2026)
The primary objective of this narrative literature review is to critically examine the multifaceted role of foreign language acquisition across cognitive, educational, and macroeconomic dimensions, thereby evaluating its significance as a structural determinant of contemporary educational systems within a globalized paradigm. Utilizing a systematic search strategy across Google Scholar, Scopus, and Web of Science databases, a total of 320 records were screened, resulting in the final inclusion of 21 peer-reviewed studies published between 2005 and 2025. The synthesized findings demonstrate that at the individual level, multilingual competence is positively correlated with enhanced executive functioning, cognitive flexibility, metalinguistic awareness, and intercultural empathy. In educational contexts, language proficiency facilitates academic mobility and broadens access to international institutional environments. Furthermore, at the macroeconomic scale, linguistic diversity acts as a catalyst for transnational trade flows, cross-border knowledge transfer, and diplomatic cooperation. Conclusively, the evidence indicates that foreign language education transcends basic communicative utility, serving as a strategic component of human capital formation and socio-economic integration.